Acclimation of Hairless Spontaneously Hypertensive Rat to Ambient Temperature Attenuates Hypertension-Induced Pro-Arrhythmic Downregulation of Cx43 in the Left Heart Ventricle of Males - Katarina Andelova; Matus Sykora; Veronika Farkasova; Tatiana Stankovicova; Barbara Szeiffova Bacova; Vladimir Knezl; Tamara Egan Benova; Michal Pravenec; Narcis Tribulova (Biomolecules)
Objectives: Due to poor treatment adherence and lifestyle-based interventions, chronic hypertension is a dominant risk factor predisposing individuals to heart failure and malignant arrhythmias. We investigated the impact of the postnatal acclimation of hairless SHR to ambient temperature that is, for them, below thermoneutrality, on the electrical coupling protein connexin-43 (Cx43) and pro-fibrotic markers in both heart ventricles of male and female hairless SHR rats compared to the wild SHR. Methods: Some 6-month-acclimated male and female hairless SHR as well as age- and sex-matched wild SHR were included and compared with the non-hypertensive Wistar strain. The left and right heart ventricles were examined for Cx43 topology, myocardial structure, and the histochemistry of capillaries. The protein levels of Cx43, relevant protein kinases, and extracellular matrix proteins (ECMs) were determined by immunoblotting. MMP-2 activity was assessed via zymography, and susceptibility to malignant arrhythmias was tested ex vivo. Results: Cx43 and its phosphorylated variant pCx43368 were significantly reduced in the left heart ventricles of wild SHR males, while to a lesser extent in the hairless SHR. In contrast, these proteins were not significantly altered in the right heart ventricles of males or in both heart ventricles in females, regardless of the rat strain. Pro-arrhythmic Cx43 topology was detected in the left heart ventricle of wild SHR and to a lesser extent in hairless SHR males. TGFβ protein was significantly increased only in the left ventricle of the wild SHR males. MMP-2 activity was increased in the right ventricle but not in the left ventricles of both males and females, regardless of the rat strain. Conclusions: The findings indicate that the postnatal acclimation of hairless SHR to ambient temperature hampers the downregulation of Cx43 in the left heart ventricle compared to wild SHR males. The decline of Cx43 was much less pronounced in females and not observed in the right heart ventricles, regardless of the rat strain. It may impact the susceptibility of the heart to malignant arrhythmias.